STRUCTURE OF TRAINING LOADS OF MIDDLE DISTANCE RUNNERS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, it is considered that the specific main characteristics of the loads used by middle-distance runners should be studied.